Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1073/pnas.2220320120
|View full text |Cite
|
Sign up to set email alerts
|

Functional SARS-CoV-2 cross-reactive CD4 + T cells established in early childhood decline with age

Abstract: Pre-existing SARS-CoV-2-reactive T cells have been identified in SARS-CoV-2-unexposed individuals, potentially modulating COVID-19 and vaccination outcomes. Here, we provide evidence that functional cross-reactive memory CD4 + T cell immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is established in early childhood, mirroring early seroconversion with seasonal human coronavirus OC43. Humoral and cellular immune responses against OC43 and SARS-CoV-2 were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Previous studies have shown that elderly persons are generally more susceptible to infections and often have poorer outcomes of infections compared to younger individuals ( 1 , 2 , 17 ). Interestingly, our results also show that chronological age is an independent risk factor, also when adjustment was made for co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that elderly persons are generally more susceptible to infections and often have poorer outcomes of infections compared to younger individuals ( 1 , 2 , 17 ). Interestingly, our results also show that chronological age is an independent risk factor, also when adjustment was made for co-morbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 54 While cross reactive humoral responses have been shown not to underly this protection, 55 studies have reported pre-existing T cell responses to endemic HCoVs with cross-reactivity to SARS-CoV-2 in unexposed adults 50 , 56 , 57 , 58 , 59 , 60 , 61 and children. 22 , 24 , 62 , 63 These cellular responses were targeted mainly toward the S2 subunit which is highly conserved among coronaviruses. 22 , 25 In our study, we showed a positive correlation between the frequency of SARS-CoV-2 CD4 + T cells and the magnitude of HKU1 spike-specific IgG in SARS-CoV-2 seronegative children.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Several age-associated factors have been proposed to play a role in the reduction of severity to SARS-CoV-2 infection in children, 2 , 8 including limited comorbidities, 9 , 10 , 11 differences in the expression of SARS-CoV-2 viral entry factors, 12 , 13 , 14 robust innate immune responses, 15 , 16 , 17 , 18 humoral and cellular immunity 19 , 20 , 21 and pre-existing immunity against common cold circulating endemic HCoVs. 22 , 23 , 24 , 25 , 26 Endemic HCoVs account for 15 to 30% of respiratory infections reported annually in children. 27 , 28 These HCoVs belong to the alpha-coronavirus subfamily (HCoV-229E and HCoV-NL63) and the beta-coronavirus subfamily (HCoV-OC43 and HCoV-HKU1), are generally considered to have seasonal infection peaks during the winter season and are responsible for high rates of infection among children.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, memory T cells generated following HCoV infections are able to cross-react with SARS-CoV-2 antigens, as demonstrated using pre-pandemic samples, in both adults and children. 3941 This cross-reactivity is established very early in life. 39 However, despite numerous HCoV exposures, Humbert et al showed the capacity of T cells to cross-react declines with age, as does the capacity of CD4 + T cells to respond to HCoV.…”
Section: Discussionmentioning
confidence: 99%
“…3941 This cross-reactivity is established very early in life. 39 However, despite numerous HCoV exposures, Humbert et al showed the capacity of T cells to cross-react declines with age, as does the capacity of CD4 + T cells to respond to HCoV. 39,41 In line with this, we report that the increased level of T-cell memory observed in adults is unique to SARS-CoV-2 and is not seen when evaluating responses to other seasonal HCoV, as demonstrated by their lower level of response to HCoV-HKU1 and HCoV-OC43.…”
Section: Discussionmentioning
confidence: 99%